What explains the uptake of development interventions? - Lennart Kaplan; Jana Kuhnt; Katharina Richert; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2019)
A crucial prerequisite for the success of development interventions is their uptake in the targeted population. We use the setup of an intervention conducted in Indonesia and Pakistan to investigate dis-/incentivizing factors for program's uptake and support. Making use of a framework grounded in psychological theory, "The Theory of Planned Behaviour", we consider three determinants for intervention uptake: personal attitudes, the social influence of important others and the perceived ease of intervention use. As most development interventions are characterized by a cooperation among local and international agents, we investigate further a potentially important dis-/incentivizing factor: the salience of the implementer's background. Our findings show that attitudes, important others and ease of intervention use are indeed associated with increased uptake in our two culturally different settings. Conducting a framed field experiment in Indonesia we show further that the study population in the Acehnese context exhibits higher levels of support for the project if the participation of international actors is highlighted. We find that previous experience with the respective actor is pivotal. To strengthen supportive behaviour by the target population for locally led projects, it is essential to strengthen local capabilities to create positive experiences. Hence, our results encourage development research and cooperation, first, to consider personal attitudes, the social influence of important others and the perceived ease of intervention use in the design of interventions in order to increase uptake. Second, depending on the country context, implementers should consider the previous experience with and attitude towards partners - either local or international - when aiming to achieve behavioural change.
Keywords: 330; Theory of Planned Behaviour; Framed Field Experiment; Implementation Research; Public Health